The role of Ukrainian folk art in forming ethno-cultural identity of a person - Otych, O (Professional Pedagogics, 2011)
The scientific analysis of essence and maintenance of ethno-cultural authentication is conducted in the article, the importance of folk art in forming national character and mentality of people is shown. A con- clusion about the necessity of development and introduction of events concerning protection and translation of ethnic culture as the most important incarnation and criterion of a nation’s uniqueness and basis of its spi- rituality in vocational training of students of vocational and vocational-art schools is done.
Keywords: national culture; etnokultural authentication; folk art; professional school